2008
DOI: 10.1007/s00128-008-9585-4
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of DNA Barcoding in Ecotoxicological Investigations: Resolving Taxonomic Uncertainties Using Eisenia Malm 1877 as an Example

Abstract: Standard test species may differ in their response to toxicants. Accurate identification of test organisms is therefore of critical importance in correctly interpreting data generated from laboratory assays. This is not always possible when species are morphologically similar or where the taxonomy of the group has recently been revised. A case in hand concerns Eisenia sp. Based on recent genetic evidence two species, Eisenia andrei and Eisenia fetida, which were previously considered a single species, are curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 6 publications
2
11
0
Order By: Relevance
“…Two very divergent haplotypes of E . fetida COI sequences were detected also during other studies [ 13 , 14 , 30 ], thus this aspect is worth of further investigation. Remarkably, specimens of the molecular E .…”
Section: Discussionsupporting
confidence: 62%
“…Two very divergent haplotypes of E . fetida COI sequences were detected also during other studies [ 13 , 14 , 30 ], thus this aspect is worth of further investigation. Remarkably, specimens of the molecular E .…”
Section: Discussionsupporting
confidence: 62%
“…g ., [ 36 , 37 ]), and for toxicity studies involving test species commonly cultured in laboratories ( e . g ., [ 38 ]). Taxonomic uncertainty can be due to cryptic species ( i .…”
Section: Resultsmentioning
confidence: 99%
“…The eco-physiologically similar hermaphroditic earthworms, 'red worms' Eisenia andrei (Ea) and 'tiger worms' (or 'brandlings') Eisenia fetida (Ef), were originally considered as pigmentation morphs of E. fetida, and later as subspecies. Currently they are treated as two distinct species, Ea and Ef, with species-specific mitochondrial and nuclear DNA sequences [1][2][3], the latter with Ef1 and Ef2 mitochondrial lineages [4]. Studies on the breeding biology of Ea and Ef specimens from Spain and Brazil have indicated that they are reproductively isolated [5], although the isolation is incomplete [6,7].…”
Section: Introductionmentioning
confidence: 99%